Implementasi Corporate Social Responsibiliy Berlandaskan Tri Hita Karana Di Hotel Jaringan Internasional - Susanti, Christina; I Gusti Ngurah Agung Wiryanata (UHN IGB Sugriwa Denpasar, 2024)
This study aims to identify and understand the implementation of Corporate Social Responsibility (CSR) based on Balinese local culture, namely Tri Hita Karana (THK) at WS Bali Hotel. This research is a qualitative study using sources determined by purposive sampling technique. Data collection was done by interview, documentation study, and observation. Data analysis techniques used in this research are data reduction, data presentation, and conclusion drawing. The results of this study indicate that WS Bali Hotel has implemented Tri Hita Karana. Implementation of parhyangan by establishing places of worship, conducting joint religious activities in the internal and external environment of the hotel. Implementation of pawongan by helping foundations and families in need and providing facilities for employees to carry out their respective passions and the practice of giving fair rewards and punishments. Implementation of palemahan by not using single-use plastics, recycling soap and shampoo residues, recycling used cooking oil and handling waste properly. The hotel pays attention to the welfare of employees and the environment by facilitating CSR activities that run in harmony with THK which contains Balinese cultural values.